Connecting reminiscence, art making and cultural heritage: A pilot art-for-dementia care programme - Tan, Michael Koon Boon (2018)
The incidence of dementia in Singapore is increasing and strategies to care for people with dementia are necessary. Let’s Have Tea at the Museum is a pilot participatory visual art programme designed for clients at an Alzheimer’s Disease Association (ADA) Singapore day care centre. The programme, which combines reminiscence with art-making, aims at enabling participants to further explore the heritage collection at the Peranakan Museum to reawaken memories and promote personal expression. This study involved eight participants (seven females and one male) all aged 70 years and older, with early-stage or moderate-stage Alzheimer’s disease. Video recordings and journal entries were collected to study the effects of the programme on the participants. Data were analysed and interpreted using a grounded theory approach to identify general themes and facilitate focused analyses. The three themes identified in this study that support the benefits of the programme include the following: (1) fostering space for self-discovery, growth and socializing; (2) art as a resource for multi-sensorial engagement and stimulation; and (3) encouraging play and boosting morale. Further use and development of the programme is recommended as a strategy to care for and enrich the lives of people with Alzheimer’s disease.